Multicultural education as a reform initiative: alignment of critical succes domains - Suseela Malakolunthu (JOURNAL OF EDUCATION, 2010)
In the multicultural Malaysia, a new school model called the Vision School (Sekolah Wawasan) was established to foster racial coexistence and cultural pluralism among students. The Vision Schools would house all the three major vernacular (Malay, Mandarin, and Tamil) elementary schools in the same compound sharing common physical facilities and events. A qualitative study of selected Vision Schools highlights that the lofty idea of student integration for unity cannot be attained merely by physical reorganization or sporadic joint events. Successful implementation of multicultural education, just as any educational reform initiative, will require the coherent alignment of several critical action domains. And these could include principal leadership, teacher professional development, curriculum framework, pedagogical strategies, instructional materials and textbooks, and assessment. It is essential that these critical action domains are well aligned with the multicultural education initiative and aptly incorporated in the detailing process of the Vision School policy development processes